Quality of Life and It’s Association with Physiotherapy in Patients After Total Knee Replacement- a Correlational Study - Ganesh MSP (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Degenerative joint disease, or osteoarthritis, is generally the main cause of physical deficiencies among elderly people. The pain and functional limitation caused by this condition, especially in the lower limbs, present a strong correlation with reduced quality of life among these individuals. There are many factors that affect the individual quality of life after TKR like patients psychology behind surgical procedure, poor awareness about physiotherapy rehabilitation procedure. So the purpose of study was to evaluate the quality of life in patients after TKR. Aim To evaluate quality of life and its correlation with physiotherapy in patients after total knee replacement. Methods In this correlation study, 72 total knee replacement patients were taken. Collection of demographic data & Communication was done through visiting patient’s home and through telecommunication media. Patients were evaluated for quality of life using WOMAC and EQ-5D. To find out association of quality of life with physiotherapy in total knee replacement patients, 72 patients were divided in 2 groups, who received physiotherapy and who didn’t. After that results were carried out. Results Chi-square test for association between physiotherapy taken and quality of life (WOMAC) carried out, P < 0.05. Chi-square test for association between physiotherapy taken and quality of life (EQ-5D) were considered significant. ( P value is <0.05) Conclusion The patient who received physiotherapy treatment after TKA seems to show a significant improvement in quality of life. Since pain and function are the most important predictor of improved quality of life and also better dynamic balance as compared to patient who didn’t received physiotherapy protocol.